Types and Abundance of Periphyton Attached to the Pipe Substrates in the Bakuok Lake,Aur Sati Village, Tambang District, Kampar Regency, Riau Province - Gultom, Zogi Tri; Dahril, Tengku; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract            Periphyton is a microorganism that attached to submerged substrate. This research aims to determine the trophic state of the Bakuok Lake in Aur Sati Village based on periphton abundance. This reseacrh has been conducted in July-August 2019. There were 3 stations, namely Station 1 (around the plantation area), Station 2 (settlements area) and Station 3 (around the net cages area). In each station there were two sampling points, namely in the surface (15 cm depth) and 2 Secchi depths (174 cm depth). The substrate used is a pipe substrate (10x11 cm2). Substrate placement done 1 week before sampling. Sampling were conducted 3 time, once/week. The periphyton samples were obtained by spraying the pipe surface with aquadest using a plastic sprayer. . The periphyton were preserved with lugol 1% was then identified using an identification book Prescott (1974), Belcher and Swale (1978), Yunfang (1995), Biggs and Killroy (2000). Water quality parameters measured were temperature, transparency, depth, pH, dissolved oxygen, free carbondioxide, nitrate (NO3) and phosphate (PO4). Result shown  that there were 29 types of periphyton, belongs to 5 classes, namely Bacillariophyceae (14 species), Chlorophyceae (6 species), Cyanophyceae (4 species), Euglenophyceae (2 species), and  Zygnematophyceae (3 species). Periphyton abudance found during the study ranged from 10 cells/cm2-1749 cells/cm2. The most commom periphyton type was Nitzschia acicularis. Based on the type of periphyton, it was concluded that the Bakuok Lake can be catagorized as oligotrophic.  Keyword: Trophic State, Water Quality, Nitzschia acicularis